2010 International Conference on Computational Science and Its Applications 2010
DOI: 10.1109/iccsa.2010.63
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Software Effort with Minimum Features Using Neural Functional Approximation

Abstract: The aim of this study is to improve software effort estimation by incorporating straightforward mathematical principles and artificial neural network technique. Our process consists of three major steps. The first step concerns data preparation from each considered database. The second step is to reduce the number of given features by considering only those relevant ones. The final step is to transform the problem of estimating software effort to the problems of classification and functional approximation by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…When it comes to setting a threshold as minimum confidence, we try to borrow ideas from the performance assessment for effort estimation models. When assessing effort estimation models, in general, both Percentage Relative Error Deviation within x (PRED(x)) and Mean Magnitude Relative Error (MMRE) adopted 25% as measurement threshold [11,13,15]. Similarly, here we define that an association rule is acceptable if its incorrect predictions are less than 25% of applicable instances in a dataset.…”
Section: B Experimental Methods Of the Investigationmentioning
confidence: 99%
“…When it comes to setting a threshold as minimum confidence, we try to borrow ideas from the performance assessment for effort estimation models. When assessing effort estimation models, in general, both Percentage Relative Error Deviation within x (PRED(x)) and Mean Magnitude Relative Error (MMRE) adopted 25% as measurement threshold [11,13,15]. Similarly, here we define that an association rule is acceptable if its incorrect predictions are less than 25% of applicable instances in a dataset.…”
Section: B Experimental Methods Of the Investigationmentioning
confidence: 99%
“…Dasharnais is one of the most common datasets in the field of software effort estimation . Although this dataset is relatively old, it has been widely employed in many of recent research studies . In this dataset, there are 81 projects related to a Canadian software company, out of which, four projects include missing values, and the remaining 77 projects are considered in the evaluation process.…”
Section: Evaluation Processmentioning
confidence: 99%
“…Project managers (PMs) must decide what data are to be collected to suit the applicable domain. Jodpimai, Sophatsathit, and Lursinsap [15] explored the relationship of different project dimensions to select only a handful of relevant cost drivers as oppose to standard 16 factors in existing approaches, yet yielding similar outcome. The needs for standardizing its deliverables and development process are key factors to software products.…”
Section: Related Workmentioning
confidence: 99%
“…For example, the COCOMO model [3] uses 17 cost drivers in the estimation process. Jodpimai, Sophatsathit, and Lursinsap [15] found that only a handful of cost drivers were effective factors that could derive as accurate estimation as the comparative models without employing the full-fledge parameter set. Moreover, fewer cost drivers translated into faster computation time.…”
Section: Feature Selectionmentioning
confidence: 99%
See 1 more Smart Citation